2013
DOI: 10.1021/ma400238t
|View full text |Cite
|
Sign up to set email alerts
|

Ethynylene-Linked Donor–Acceptor Alternating Copolymers

Abstract: Controlling steric interactions between neighboring repeat units in donor–acceptor (D–A) alternating copolymers can positively impact morphologies and intermolecular electronic interactions necessary to obtain high performances in organic photovoltaic (OPV) devices. Herein, we design and synthesize 12 new conjugated D–A copolymers, employing ethynylene linkages for this control. We explore D–A combinations of fluorene, benzodithiophene, and diketopyrrolopyrrole with analogues of pyromellitic diimide, thienoiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 49 publications
0
49
0
Order By: Relevance
“…Besides, OSMs will receive high V OC which were benefited from the deep-lying HOMO level caused by the electron-withdrawing effect of alkyne. Hence, alkyne including acetylene and arylacetylenes is a promising class of π-bridge [78][79][80][81][82][83]. Fig.…”
Section: π-Linkage With Alkynementioning
confidence: 99%
“…Besides, OSMs will receive high V OC which were benefited from the deep-lying HOMO level caused by the electron-withdrawing effect of alkyne. Hence, alkyne including acetylene and arylacetylenes is a promising class of π-bridge [78][79][80][81][82][83]. Fig.…”
Section: π-Linkage With Alkynementioning
confidence: 99%
“…33 In this contribution, two diketopyrrolopyrrole (DPP) units are linked to the both sides of a porphyrin core to extend the π-conjugation via ethynylene bridge, whose functions are two-fold 34,35 (1) introducing sp 1 carbon hybridization can be effective in lowering the highest occupied molecular orbital (HOMO) energy level of the target materials since there are more s-orbital components; and (2) its fluent cylinderlike π-electron density is more adaptable to conformational and steric constrains, and thus to enhance inter-molecular π-π stacking and facilitate intramolecular charge transport. Since it has been reported that thienyl substituents can enhance the OSC's performance, two thienyl groups with a 2-ethylhexyl substituent are introduced into the porphyrin core with added benefit of improving material's solubility.…”
mentioning
confidence: 99%
“…Reich synthesized a 3,6 and N , N ′‐linked pyromellitic diimide polymer which gave an electron‐carrier mobility of 10 −3 to 10 −2 cm 2 V −1 s −1 when the polymer was blended with Phenyl‐C61‐butyric acid methyl ester (PC 61 BM) in a weight ratio of 1:9. This lower charge carrier mobility may be owing to the twist in the neighboring conjugated units in the polymer backbone which result in a decrease in the conjugation . Thus, the insertion of ethynyl linkages at 3,6‐positions on the pyromellitic diimides can decrease the steric and electronic repulsions and is expected to provide a more planar polymer backbone .…”
Section: Introductionmentioning
confidence: 99%